Cyberbullying Perpetration: Children and Youth at Risk of Victimization during Covid-19 Lockdown - Mkhize, Simangele; Gopal, Nirmala (International Journal of Criminology and Sociology, 2021)
The Covid-19 is believed to have emerged in Wuhan, China, and has affected many countries across the globe. In response to this pandemic, governments in different countries have implemented social distancing measures to stop the spread of the virus. The closure of schools and switch to remote learning of universities to protect youth and children from exposure to the virus might also open opportunities for certain crimes such as cyberbullying. The study aimed at exploring the risks of victimization of children and youth through cyberbullying during the lockdown. A qualitative approach, non-participant observation was utilised. Data was collected from three social media platforms which include Facebook, Twitter, and Instagram from posts since the beginning of lockdown. Keywords such as “ama2000s”, “2000s” and “90s vs 2000s” were used to search for content. Facebook groups for “2000s” where most young people engage were also used. The study found that with the increase of the use of social media among children and youth during the lockdown, most have been victims of cyberbullying. In these platforms where young people engage, most posts and comments carried content which includes sexting, sexual comments on young girls’ pictures, trending of videos of school children fighting, and insulting each other. A significant finding was the use of fake accounts to perpetrate cyberbullying. The study recommends that addressing cyberbullying through educating children and youth about acceptable online behaviour, signs of cyberbullying, responses to it, and cybersecurity should be prioritised.